I Felt Like A Mathematician: Problems and Assessment To Promote Creative Effort. Issue 1 (2nd January 2019) - Omar, Mohamed; Karakok, Gulden; Savic, Milos; Turkey, Houssein El; Tang, Gail
Abstract: Challenging mathematics problems were posed as a substantial part of homework in an elective combinatorics course. The intent was to encourage undergraduate students' exploration as well as develop their technical writing skills. The bulk of students' grades on these problems rested on a three-page reflective write-up using a rubric on mathematical creativity, the Creativity-in-Progress Rubric on Proving. Through student reflections, this structure led to a self-reported boost in students' proving confidence and led them to view themselves as practicing mathematicians. Descriptions of the problems, how students used the rubric as their guide, and grading structure are detailed in this article.